Respostas termorreguladoras de ovinos com inclusão de extrato de própolis marrom na dieta - Souza, Isis Thamara do Nascimento (2021)
The aim of this study was to evaluate the thermoregulatory responses of confined sheep in the semiarid region, when submitted to the inclusion of brown propolis ethanol extract in the diet. For this, twelve male sheep, with no defined racial pattern (SPRD) were used, weighing approximately 22kg, receiving a roughage and concentrate based diet in the proportion of 40:60. , being allowed leftovers of 10% of the total supplied. The animals were divided into two treatments, TC - without inclusion of propolis and TP - with inclusion of propolis, for the group with inclusion of propolis the extract was provided before the diet so that the total intake of the 8ml provided could be confirmed. The animals were submitted to 59 days of experiment, 14 days for adaptation and 45 days for data collection of physiological parameters. To evaluate the response of lambs to heat stress, physiological parameters were measured at three times, beginning, middle and end of the experimental period, starting at 7 am and ending at 17 hours, every 120 minutes. Respiratory rate, rectal temperature, air temperature, relative humidity and wind speed were observed. It was observed that, for the animals in the control group, the respiratory rate differed when the AT was below 28ºC and when it was above 36ºC, while for the propolis group there was a difference only when the AT was below 28ºC. For the two groups, no significant differences (P<0.05) were observed in the variable of rectal temperature. Based on the study carried out, it was observed that the inclusion of 8ml/day of 30% ethanolic propolis extract in the sheep diet allowed a smaller variation in the physiological parameters indicative of heat stress, providing a positive effect on the homeotherm of these animals